Demands of competitions of elite women world cup cycling races - Sias, M.; La Torre, A.; Menaspa, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Competition data are important to identify unique characteristics associated with successful performances. Elite women road cycling is a fast growing sport, however there is a lack of recent research (last 10 years) focusing on performances at International level. The aim of this study was to compare the physiological demands of recent women`s World Cup races (2012-15) finishing with top 10 (T10) and out of top 10 (N-T10) results. Methods: Seven female professional cyclists (mean±SD; age: 28.5±2.9 years; body mass: 55.7±3.9 kg; height: 165±4 cm) participated to this study. The participants` bikes were fitted with SRM powermeters. Forty-nine road World Cups (WC) were analysed, with 25 top T10 and 24 N-T10 race results. Race files were analysed with the open-source software GoldenCheetah. Descriptive statistics were used to report race characteristics such as length, duration and elevation gain. Maximal Mean Power curves (Quod et al. 2010) and % of total time spent in different power to weight bins (Martin et al. 2001) were compared in T10 and N-T10 with unpaired t-tests. Effect sizes were calculated and presented to allow a better interpretation of the results. The values 0.2, 0.5 and 0.8 were considered respectively small, medium and large (Sullivan et al. 2012). Statistical significance was set at P<0.05. Results: World Cups` average distance was 128±7 km, with a duration of 3h20min±16 min and a total elevation gain of 998±551 m. The average power recorded was similar with 184±22 and 185±16 W for T10 and N-T10, respectively. Maximal Mean Powers for durations between 10 and 600 s were significantly higher in T10 than in N-T10 (P<0.05), with a large effect size for durations between 20 and 300 s. There was no difference in the % of total time spent below 0.75 W/kg (21±4 and 19±4 min for T10 and N-T10, respectively) (P=0.23). T-10 spent significantly more time above 7.5 W/kg when compared to N-T10 (6±2 and 4±2 min, respectively) (P=0.005), with a medium effect size. Discussion: In WC races Maximal Mean Power between 20 and 300 s were the main performance discriminant differentiating T10 and NT10.. Maximal Mean Power data found in this study were comparable to the data reported by Ebert et al. (2005) in top 20 WC races. The average power output found in this study was 10% higher than the power recorded in a previous study on domestic Australian competitions (Abbiss et al. 2010). Cyclists achieving T10 results spent more time above 7.5 W/kg when compared to N-T10, which seems to be a key factor determining the demands of T10 WC competitions. The findings of the present investigation should be considered for training prescription and selection purposes.